Investigating the effects of surface moisture content on thermal infrared emissivity of urban underlying surfaces. (11th April 2022) - Zhong, Xue; Zhao, Lihua; Zhang, Xiang; Yan, Junru; Ren, Peng
Highlights: The SMC-sensitive bands of underlying surfaces containing quartz range from 8.0 to 10.0 μm. The larger the SMC, the higher the emissivity, particularly evident in the SMC-sensitive bands. SMC exerts little effect on the emissivity (8.0–13.5 μm) of permeable materials. SMC exerts a notable effect on the emissivity (8.0–13.5 μm) of surfaces with original lower emissivity. The sigmoidal model is optimal in characterizing variations of soil emissivity with SMC. Abstract: As an inherent property of materials, emissivity critically reflects the material composition. Despite evidence on the positive correlation between surface moisture content (SMC) and the emissivity for soil, such correlations for other urban underlying surfaces have not been examined. Accordingly, this paper aimed to investigate the effects of SMC on the emissivity of ten representative urban underlying surfaces (including impervious and permeable ones), through comparisons of their emissivity spectra before and after water-sprinkling. Based on the spectra, the sliding-window algorithm was used to identify SMC-sensitive bands of the surfaces, whose increments of emissivity within the SMC-sensitive and 8.0 – 13.5 μm bands were analyzed. Furthermore, for soil, models characterizing the relationship between its SMC and emissivity were established. The results showed that the emissivity of most underlying surfaces increased with SMC, which was particularly evident in the SMC-sensitive bands (8.0 – 10.0 μm). Additionally, the impacts of SMC on emissivity (8.0 – 13.5 μm) depend on the properties of the surfaces. SMC critically influenced the emissivity (8.0 – 13.5 μm) of the concrete pavement, granite pavement, asphalt road and soil: their increment exceeded 0.02, which could lead to substantial fluctuations in retrieving temperature (0.9, 2.1, 1.0 and 2.3 K, respectively). However, SMC was found to exert little effect on the emissivity (8.0 – 13.5 μm) of the permeable brick pavement, gravel road, red clay brick pavement, grasses and shrubs. Lastly, variations in emissivity of the soil with SMC were optimally characterized by the sigmoidal model, whose correlation was the highest (adjusted-R 2 = 0.9848).